Elderly Hip Osteoarthritis: A Review of Short-Term Pain Relief Through Non-Weight-Bearing Therapies - Olivia Norato; Sarah Velez; Arbonor Lleshi; Gordon Lam; Marlon Morales; Glory Udechi; Edwin Cung; Jean-Philippe Berteau (Journal of Functional Morphology and Kinesiology)
Older individuals with hip osteoarthritis (OA) who have difficulty walking, climbing stairs, or performing daily tasks often find non-weight-bearing (NWB) exercises essential for rebuilding strength and preserving function without further stressing the joints. In addition, those with a higher body mass index (BMI) particularly benefit from NWB therapy, as it alleviates joint pressure while facilitating safe and effective rehabilitation. Thus, NWB interventions, such as manual therapy (MT) and aquatic therapy (AT), are especially critical for older adults aged 60 and above, offering pain relief and functional improvement by minimizing gravitational impact on the hip joint. This review examines the effectiveness of these approaches in managing hip OA symptoms and decreasing pain. The inclusion criteria for the study consisted of randomized controlled trials or controlled trials focused on adult patients with primary osteoarthritis of the hip joint, utilizing interventions such as MT (including thrust joint mobilizations, non-thrust/oscillatory mobilizations, and soft tissue mobilization) or AT (including hydrotherapy and water therapy), and assessing outcomes related to pain. We selected nine studies that included a total of n = 1037 individuals. It evaluated outcomes such as self-reported pain levels using measures like the Western Ontario and McMaster Universities Osteoarthritis (WOMAC), Numeric Rating Scale (NRS), and Visual Analog Scale (VAS). Beyond statistical differences, both therapies were evaluated for Minimal Clinically Important Difference (MCID). While MT studies indicated a decrease in pain according to pain index scores, they showed short-term effectiveness till five weeks but lacked sustained clinical efficacy beyond this period. AT showed positive results within a ten-week period, although its effectiveness seemed to level off beyond this duration, falling below the threshold of clinical efficiency. After 10 weeks of treatment, there is no discernible clinical benefit in terms of pain reduction. Both interventions without gravitational impact seem suitable for providing short-term pain relief for primary hip osteoarthritis patients, but long-term pain relief—meaning after ten weeks—should be maintained through therapeutic exercise and patient education.